THE SOME PROBLEM OF A MODEM MUSICAL-PERFORMING ART - Byelikova, V.V. (Pedagogy of Higher and Secondary Education, 2007)
The author of article accents attention of the reader to perusal and interpretations o f the musical text of vocal product, problems of a modern musical-performing art as such is lighting.